Overweight in Rural Quilombola and Non-quilombola Adolescents From the Northeast of Brazil - Cairo, Stefanie M. C.; Teixeira, Camila S. S.; da Silva, Tainan O.; da Silva, Etna K. P.; Martins, Poliana C.; Bezerra, Vanessa M.; de Medeiros, Danielle S. (Frontiers in Nutrition, 2021)
Introduction: Overweight is an emerging problem among children and adolescents that leads to the development of several morbidities and health risks. Overweight occurs differently in different populations, especially in vulnerable groups like the rural and quilombola communities (an African-descendant population). This study aimed to estimate the prevalence of overweight and to investigate the possible associated factors in rural adolescents living in both quilombola and non-quilombola communities in Northeast Brazil. Methods: This study is a population-based cross-sectional study with a household approach, carried out in 2015 with 390 adolescents (age 10–19 years) living in rural quilombola and non-quilombola communities. The nutritional status was gauged using z-scores calculated for BMI and varies with gender and age. Prevalence ratios and 95% confidence intervals were used to establish associations between the results and explained variables. The multivariate analysis followed a model with a hierarchical entry of covariables, controlled by gender and age. Results: The study showed that 18.5% of rural adolescents were overweight, of which 17.9% were quilombolas and 19.0% non-quilombolas. A significant difference in overweight between the samples was not found. In the multivariate-adjusted model, age ≥ 16 years (PR: 0.51; CI: 0.28–0.95), the habit of having regular breakfast (PR 0.58; CI 0.35–0.98), and process of attending school (PR 0.35; CI 0.17–0.71) were associated with a lower prevalence of overweight. Stationary screen time, in contrast, was associated with a higher prevalence (PR 1.61; CI 1.05–2.46). The process of attending school was associated with a lower prevalence of overweight (PR 0.26 CI 0.09–0.69), even for the quilombolas. Conclusions: A low prevalence of overweight was identified in rural adolescents. Overweight was significantly associated with the habit of having regular breakfast, older age, stationary screen time, and the process of attending school. The results reveal that school is a potential space for health promotion interventions, specifically in the most vulnerable rural regions, such as the quilombola communities. Besides, the study emphasizes the importance of adopting a healthy lifestyle early in life, including, cultivating the habit of having regular breakfast and reducing stationary screen time.